Penerapan Metode Perbandingan Eksponensial pada Sistem Pendukung Keputusan untuk Menentukan Pegawai Terbaik - Nurmala Plorensia Br Aritonang; Fauriatun Helmia; Rohminatin Rohminatin (Universitas Hamzanwadi, 2024)
The Department of Animal Husbandry and Health of Asahan Regency is a government agency that conducts education and health checks for animals. Employee assessment in this department is conducted to determine the quality of staff. However, the current assessment process is still manual using assessment sheets and remains subjective. The aim of this research is to develop a decision support system by applying the Exponential Comparison Method (ECM) to determine the best employees. We utilized the waterfall model to build this system, involving stages of analysis, design, implementation, and testing. The analysis stage was conducted to gather the necessary data for system development, processed using the ECM method. For the design stage, we presented flowcharts, data flow diagrams (DFD), and use case diagrams. In the implementation stage, we developed an application using the web programming language PHP with a MySQL database. System testing employed black box testing to assess the functionality of all system components. Our findings revealed Herman Sitepu as the top-ranking employee. The system, presented as a web application with multiple menus, performed well based on black box testing results. Consequently, this system can be used to evaluate employee performance at the Department of Animal Husbandry and Health of Asahan Regency.